APPLICATION OF RESISTIVITY AND INDUCED POLARIZATION METHOD TO DETECTING MINERALIZED ZONE 'MUTANT' FIELD - NATALIUS (NIM: 123 06 039), ALVIN
Geophysic‟s research of Induced Polarization (IP) method is an applicative field study and scientific approach in describing the condition of earth‟s subsurface. It‟s effort to prospect the potential of gold mineralization ore body based on variation of resistivity value (ohm.m), Percent Frequency Effect (PFE) (%) and Metal Factor (MF) (mohs/m). This research was conducted in gold prospect area Ã‚Â“MUTANTÃ‚Â”. The used data are 6 lines i.e : PKS 0, PKS -4, PKS -6, PKS +1, PKS +3 and PKS +7 They were obtained by data acquisition using frequency domain IP measurement technique. The electrode configuration that was applied in this research is dipole-dipole array with 50m spacing. The value of Ã‚Â“nÃ‚Â” measurement was until Ã‚Â“n-6Ã‚Â”. Data processing was conducted using software of Surfer Version 8.0 and Res2dinv version 3.54. Analyses and reviews of two dimensional IP resistivity inversion modeling in data processing inform that resistivity values of lithologies in mineralization zone are differ according the influence of many factors such as mineralization intensity and the hostrock type. The analyses on two dimensional IP MF and PFE inversion modeling was applied to prospect the potential of mineralization ore body. Theoretically, ideal condition of sulfide mineralization ore body (with potential gold associations) was shown by the MF anomaly value in research area of >100 mohs/m, PFE value ( 2 Ã‚Â– 5 ) % and was overlapped with the low resistivity value (<100 ohm.m). Nevertheless, supported by other exploration data (surface geology and magnetic), A conclusion was obtained that generally, gold mineralization ore body (veins of silification/quartz) in research area was in small dimension, disseminated spreading, and available in sulfide mineralization zones and different hostrock areas.